Biohydrogen production from dairy industry wastewater in an anaerobic fluidized-bed reactor - Silva, Aline Neves da; Macedo, Williane Vieira; Sakamoto, Isabel Kimiko [UNESP]; Dalmao Pereyra, Daniela de Los Angeles; Mendes, Camila Oliveira; Maintinguer, Sandra Imaculada [UNESP]; Caffaro Filho, Roberto Augusto; Zamariolli Damianovic, Marcia Helena; Amancio Varesche, Maria Bernadete [UNESP]; Cavalcante de Amorim, Eduardo Lucena (Elsevier B.V., 2019)
The present study evaluated the influence of organic loading rate in biohydrogen production from dairy wastewater in an anaerobic fluidized-bed reactor inoculated by natural fermentation of the wastewater used during the operational period. The support material for biomass adhesion was shredded fire. The reactor had a working volume of 908.4 cm(3). Biohydrogen production was evaluated using three different organic loading rates (OLR) of 28.7 kgCOD m(-3)d(-1), 53.2 kgCOD m(-3)d(-1) e 101,7 kgCOD m(-3)d(-1) corresponding to the Hydraulic Retention Time (HRT) of 8h (2.7 L d(-1)), 6h (3.6 L d(-1)) and 4h (5.4 L d(-1)), respectively. The hydrogen yield decreased with increasing organic loading rate (OLR) from 2.56 +/- 0.62 mol H-2 mol carbohydrate(-1) to 0.95 +/- 0.28 mol H-2 mol carbohydrate(-1) as the OLR increased from 28.65 kgCOD rn(-3)d(-1) to 95.76 kgCOD m(-3)d(-1). The hydrogen content in the biogas (volume of H-2/volume of biogas) produced and the highest volumetric production were respectively 35.72 +/- 9.43% and 0.80 +/- 0.21 LH2 h(-1)L(-1) obtained when the OLR was 53.25 +/- 7.81 kgCOD m(-3)d(-1). The main metabolites produced were acetic acid (67.15%-87.42%) and ethanol (6.01%-13.09%). Increasing the applied OLR also caused an increase in bacterial diversity as evidenced by the highest value of the Shannon-Wiener index (2.811) corresponding to the operational phase of the highest OLR (95.76 +/- 29.10 kgCOD m(-3)d(-1)).
Keywords: Anaerobic digestion; Hydrogen production; Daily wastewater